Penguatan Kompetensi Guru Sekolah Menengah melalui Pelatihan Canva untuk Peningkatan Media Pembelajaran Interaktif - Mahande, Ridwan Daud; Ashari, Hilda; Malago, Jasruddin Daud; Bakri, Hasrul; Mappangara, Surianto (Jurusan Teknik Informatika dan Komputer, 2025)
Responding to the growing demand for interactive, digital-based learning environments, this community service program was designed to strengthen the capacity of secondary school teachers to design visual learning media using Canva. Many teachers in the target areas previously relied on conventional methods and lacked exposure to digital design tools, resulting in monotonous teaching delivery and low student engagement. Through structured stages—including socialization, training, technology implementation, mentoring, and sustainability efforts—participants were equipped with the knowledge and skills to produce infographics, presentations, worksheets, and other teaching materials. Observations during implementation showed increased teacher confidence and creativity, improved student responsiveness, and improved media alignment with curriculum objectives. Teachers also informed to form a peer-to-peer digital community to ensure ongoing support and resource sharing. The program successfully addressed gaps in digital literacy and instructional design, fostering a culture of innovation and collaboration among educators. The results demonstrate that scalable, context-based interventions can make a meaningful contribution to educational transformation.